قاعدة: "التّفسير الذي فيه تطهير للأنبياء عمّا لا ينبغي أولى من غيره" عند القرطبي من خلال كتابه الجامع لأحكام القرآن - شواش عادل (University of Eloued جامعة الوادي, 2024)
الأنبياء صلوات الله عليهم سفراء الله إلى عباده؛ بعثهم مبشّرين ومنذرين، فهم متّصفون بالأمانة والصِّدق في تبليغ شريعة الله؛ لذا وجب الإيمان بعصمتهم، ونفي كلّ ما يطعن في شخصهم وأخلاقهم، من أجل ذلك ردّ المفسِّرون كلّ قول طاعنٍ في ذاتهم؛ لأنّ الطّعن فيهم ضربٌ في صدق الرِّسالة. والإمام القرطبي رحمه الله تعالى ممّن نذر نفسه للدِّفاع عن الأنبياء والرُّسل بصفة عامّة، وعن النّبيِّ صلّى الله عليه وسلّم بصفة خاصّة؛ لكثرة حملات الطّعن والتَّشكيك فيه باعتباره خاتم الأنبياء والمرسلين. ومن هنا يمكن طرح التّساؤل التّالي: كيف تعامل الإمام القرطبي رحمه الله تعالى مع القاعدة التّفسيريّة: "التّفسير الذي فيه تطهير للأنبياء عمّا لا ينبغي أولى من غيره"؟ وما مدى تطبيقه لها في تفسيره؟ وكيف ردّ رحمه الله تعالى الأقوال التي لا تُناسب مناصب الأنبياء صلوات ربّي وسلامه عليهم أجمعين؟ وللإجابة عمّا سبق ذكره انتظم البحث في مقدّمة وعرض وخاتمة. The prophets, may God’s blessings be upon them, are God’s ambassadors to His servants; God Almighty has sent them as good tidings and warnings to the servants. They are characterized by honesty and truthfulness in conveying God’s laws; Therefore, it is necessary to believe in their infallibility, and to deny everything that afflicts their person and morals, for this reason the commentators rejected every self-defaming statement; Because slandering them is a blow to the sincerity of the message. And Imam al-Qurtubi, may God have mercy on him, who dedicated himself to defending the prophets and messengers in general, and the Prophet, may God bless him and grant him peace, in particular; Due to the many campaigns of slander and questioning of him as the seal of the prophets and messengers. Hence, the following question can be posed: How did Imam al-Qurtubi, may God have mercy on him, deal with the exegetical rule: “The interpretation in which the prophets are purified from what is not appropriate is more important than others”? What is the extent of its application in its interpretation? And how did he, may God Almighty have mercy on him, respond to statements that do not fit the positions of the prophets, may the prayers and peace of my Lord be upon them all? To answer the foregoing, the research was organized into an introduction, presentation, and conclusion.
Keywords: القرطبي; الترجيح; تطهير; الأنبياء; weighting; al-Qurtubi; disinfection; the prophets